EEG-derived brain connectivity in theta/alpha frequency bands increases during reading of individual words - Fatemeh Delavari; Zachary Ekves; Roeland Hancock; Gerry T. M. Altmann; Sabato Santaniello (Cognitive Neurodynamics, 2025)

Development of the prosencephalic structures, ganglionic eminence, basal ganglia and thalamus at 11 + 3 to 13 + 6 gestational weeks on 3D transvaginal ultrasound including normative data - R. Altmann; T. Rechberger; C. Altmann; L. Hirtler; I. Scharnreitner; P. Stelzl; S. Enengl (Brain Structure and Function, 2023)
Objectives To show the development of ganglionic eminence, basal ganglia and thalamus/hypothalamus in week 11 + 3 to 13 + 6 by transvaginal 3D ultrasound. Methods To visualize the prosencephalic structures surrounding the 3rd ventricle, 285 three-dimensional ultrasound volume blocks from 402 fetuses examined were selected in a prospective transvaginal 3D study to compare ultrasound images of ganglionic eminence, basal ganglia, thalamus/hypothalamus with embryological sections. In addition, measurements of the described structures were made in 104 fetuses to quantify the embryological development. Results The sonomorphologic characteristics of ganglionic eminence, basal ganglia and thalamus/hypothalamus are described in 71% of the fetuses examined. Measurements of the structures in 57% of the fetuses, show the following results: axGE ap = 0.17 + 0.112*CRL; axGE/I = 0.888 + 0.048*CRL; axGE/BG = 0.569 + 0.041*CRL; coGE/BG = 0.381 + 0.048*CRL; coTh lat = − 0.002 + 0.135*CRL; coTh/HyT = 3.68 + 0.059*CRL; co3.V lat = 0.54 + 0.008*CRL. Conclusion Transvaginal 3D neurosonography allows visualization and measurement of normal structures in the fetal prosencephalon at 11 + 3 to 13 + 6 weeks of gestation (GW) including details of ganglionic eminence (GE), basal ganglia (BG), and thalamus/hypothalamus (Th/HyT). Further scientific work is needed before using the results to decide on pathological changes in patients.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Improved Automatic Segmentation of White Matter Hyperintensities in MRI Based on Multilevel Lesion Features - M. Rincón; E. Díaz-López; P. Selnes; K. Vegge; M. Altmann; T. Fladby; A. Bjørnerud (Neuroinformatics, 2017)

Dent and Flint maize diversity panels reveal important genetic potential for increasing biomass production - R. Rincent; S. Nicolas; S. Bouchet; T. Altmann; D. Brunel; P. Revilla; R. A. Malvar; J. Moreno-Gonzalez; L. Campo; A. E. Melchinger; W. Schipprack; E. Bauer; et al. (Theoretical and Applied Genetics, 2014)

The Arabidopsis PHD-finger protein SHL is required for proper development and fertility - C. Müssig; A. Kauschmann; S. D. Clouse; T. Altmann (Molecular Genetics and Genomics, 2000)